Techno-economic and environmental potential of Renewable Diesel as complementation for diesel and biodiesel in Brazil: A comprehensive review and perspectives. (15th October 2022) - Julio, Alisson Aparecido Vitoriano; Milessi, Thais Suzane; Ocampo Batlle, Eric Alberto; Silva Lora, Electo Eduardo; Yepes Maya, Diego Mauricio; Escobar Palacio, José Carlos
Abstract: The increasing global demand for energy and the environmental impacts of fossil fuels has brought attention to the need for a energy transition, and much attention has been given to biofuels. Special attention should be given to biofuels for heavy-duty vehicles since this sector contributes to a significant amount of CO2 emissions in Brazil. Biodiesel has an established and growing industry in Brazil. However, the limited production capacity and its limitations, such as low storage stability, highlight the need for exploring new biofuels with enhanced properties. In this sense, this work aims to make a case for Renewable Diesel as an alternative, representing an environmental and technical asset that should be explored in the eyes of the Brazilian Biofuel Policy (RenovaBio) to meet the environmental goals. This work explores the differences among Renewable Diesel, biodiesel, and petrodiesel properties and critically evaluates different routes of Renewable diesel conversion, its challenges, and the emissions to support decision-making toward the modernization of biofuels. Based on a measurable score, Renewable Diesel was 50% environmentally better than Diesel and presented more optimistic perspectives for the future than biodiesel, demonstrating suitability with the current market. Graphical abstract: Image 1 Highlights: Renewable Diesel can overcome the challenges faced by Biodiesel. Old heavy-duty engines decarbonization in Brazil must begin with better biofuels. Biodiesel will become less appealing when Renewable Diesel hits market. Public policy must foment technological development to overcome idle capacity. Renewable Diesel is 50% superior environmentally than Diesel regardless of route.